The Analysis of Students' High Level Thinking Ability on Motion Systems Material on Covid Pandemic 19 at Madrasah Aliyah Medan City - Willyana Utari Siahaan; Herbert Sipahutar; Syahmi Edi (BIRCU, 2021)
This study aims to: (1) Know the description of higher order thinking skills in the material of motion systems in students at MAN 1 Medan City. (2) Knowing the description of high-order thinking skills in the material of motion systems in students at MAL UINSU Medan City. (3) Knowing the differences in higher-order thinking skills in the material of motion systems in students at MAN 1 Medan and MAL UINSU Medan. (4) Knowing the learning process of the motion system during the COVID 19 pandemic at MAN 1 Medan and at MAL UINSU Medan. This research method uses a quantitative research type with a descriptive approach. The results showed: (1) Students 'high-order thinking skills on motion system material in class XI MAN 1 Medan City had an average score of 84.83 in a good category. (2) Students' high-order thinking skills on movement system material in class XI MAL UINSU Medan City average score of 82.17 with good category. (3) (1) Students 'high-order thinking skills on motion system material in class XI MAN 1 Medan City with an average score of 84.83 in the good category, (2) Students' high-order thinking skills on motion system material in class XI MAL UINSU Medan City an average score of 82.17 with good category. (3) With the Sig (2-tailed) value of 0.048 is smaller than the significant levels of 0.05 and nt value> t table (2.125> 2,048). (4) The highest indicator of students 'high-order thinking skills in class XI MAN 1 Medan City is creating, while the highest indicator of students' high-order thinking skills in class XI MAL UINSU Medan City.